Data Acquisition System for Exothermic and Endothermic Reaction: A Novel Laboratory Approach in Chemistry Learning - Siti Nuryani; Ijang Rohman; Miarti Khikmatun Nais; Gun GUn Gumilar; Muhamad Nurul Hana (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
The determination of exothermic and endothermic reactions using conventional thermometers is often constrained by limitations in visualization and objectivity during practical activities. This study aims to investigate the performance of a DAS as an alternative for classroom practical work. The method involved characterizing thermal dynamics through a Design Science Research (DSR) approach using the MEDS evaluation framework. To record real-time temperature profiles, a thermistor sensor was integrated into the Mixer Mini and MGA as the DAS. Calcium carbide reaction and urea dissolution were utilized as the thermochemical systems. The analysis results show that the DAS: (1) is capable of detecting phenomena that go undetected using conventional methods; (2) exhibited strong baseline stability during the pre-reaction phase with a slope approaching zero and high reliability under homogeneous conditions, indicated by RSD values of 0.45% and 3.44% for urea dissolution and the calcium carbide-water reaction, respectively; and (3) showed stable internal consistency despite deviations from literature values caused by external factors. The novelty of this research lies in the operational efficiency of a self-contained measurement system that operates without the need for coding procedures. Consequently, the DAS provides a practical, objective, and scientifically valid solution to enhance data integrity in thermochemical analyses.